2018
DOI: 10.4084/mjhid.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

Decolonization of Intestinal Carriage of MDR/XDR Gram-Negative Bacteria With Oral Colistin in Patients With Hematological Malignancies: Results of a Randomized Controlled Trial

Abstract: BackgroundIntestinal colonization by MDR/XDR gram-negative bacteria leads to an increased risk of subsequent bloodstream infections (BSI) in patients receiving chemotherapy as a treatment for hematologic malignancies.ObjectivesThe objective of this study was to evaluate the efficacy of oral colistin in eradicating the intestinal carriage of MDR/XDR Gram-negative bacteria in patients with hematological malignancies.MethodsIn a tertiary hematology center, adult patients with intestinal colonization by MDR/XDR Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Numerous decolonization studies have been undertaken, including selective digestive decontamination with colistin or aminoglycosides ( Machuca et al., 2016 ; Stoma et al., 2018 ), custom-made bacteriophage ( Hua et al., 2017 ; Corbellino et al., 2020 ; Liu et al., 2021 ) and fecal microbiota transplantation (FMT) ( Alagna et al., 2020 ; Gouveia et al., 2020 ; Ueckermann, et al., 2020 ). Although those methods demonstrated some decolonization effects, the possibility of drug resistance induced by gentamycin or colistin, the high cost and prolonged waiting time for phage, and the possibility of infectious agent transmission accompanied by FMT rendered them impractical for generalization.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous decolonization studies have been undertaken, including selective digestive decontamination with colistin or aminoglycosides ( Machuca et al., 2016 ; Stoma et al., 2018 ), custom-made bacteriophage ( Hua et al., 2017 ; Corbellino et al., 2020 ; Liu et al., 2021 ) and fecal microbiota transplantation (FMT) ( Alagna et al., 2020 ; Gouveia et al., 2020 ; Ueckermann, et al., 2020 ). Although those methods demonstrated some decolonization effects, the possibility of drug resistance induced by gentamycin or colistin, the high cost and prolonged waiting time for phage, and the possibility of infectious agent transmission accompanied by FMT rendered them impractical for generalization.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of selective digestive decontamination have shown limited short-term effectiveness in suppression of resistant organisms. [139][140][141][142][143] However, using oral antibiotics for decolonization is not routinely recommended because of the transient nature of these effects and concerns related to the emergence of resistance to the agents used for decolonization and detrimental consequences to the gut microbiome. 144 Fecal microbiota transplantation is another emerging strategy that could suppress colonization with resistant bacteria.…”
Section: Screening For Colonization With Resistant Bacteriamentioning
confidence: 99%
“…Theoretically, identifying colonization with a resistant gut organism could allow for decolonization to prevent translocation of bacteria into the bloodstream during neutropenia. Studies of selective digestive decontamination have shown limited short‐term effectiveness in suppression of resistant organisms 139–143 . However, using oral antibiotics for decolonization is not routinely recommended because of the transient nature of these effects and concerns related to the emergence of resistance to the agents used for decolonization and detrimental consequences to the gut microbiome 144 .…”
Section: Interventions To Curb the Impact Of Antimicrobial Resistancementioning
confidence: 99%